Digital activism: Unilever and the 'Kodaikanal Won't' campaign - Chaudhri, Vidhi A. (Henry Stewart Talks, 2022)
This case study describes the use of digital and social media made by a local NGO in applying pressure on multinational corporation Unilever to both clean up a contamination affecting the region and compensate local workers who had been impacted.